An Analysis of Pakistan’s National Curriculum of Mathematics at Secondary level - Rind, Amjad Ali; Mughal, Shahid Hussain (Electronic Journal of Education, Social Economics and Technology, 2020)
The purpose of the study were to analyze the Curriculum document of National Curriculum of mathematics of secondary grades. The study employed qualitative research paradigm within it the discourse analysis technique was used to analyze the mathematics curriculum document. Discourse analysis helps in understanding the written, spoken and signs language used in any document analysis. The sample of the study were foreword, introduction, objectives, reviewer’s notes and list of reviewers, the sections of mathematics in the national curriculum of mathematics (2006) for secondary grades. The findings of the study revealed that the National Curriculum of mathematics (NCM) 2006 was focused on transfer of Knowledge. However, it neglected the conceptual understanding of essential subject matter. It has been also discovered that the content of the mathematics is not taught according to the prescribed curriculum. Moreover, standard were not implemented properly. The role learners were recipient of knowledge and that of teachers is transmitter .Thus, it neglected the participatory and constructive approach of teaching and learning mathematics. Moreover, the curriculum ideology was not considered while developing the mathematics curriculum. It is suggested that the curriculum developers should revisit the policy on social constructive approach so that curriculum can be taught conceptually rather than standard based. Moreover, formative assessment should be included throughout the year rather taking annual examinations. It is recommended that teachers should impart mathematics education by linking math to social context and encourage students to construct meanings socially.